Burnout in healthcare – the Emperor’s New Clothes - Wojciech Marlicz; Anastasios Koulaouzidis; Dafni Charisopoulou; Janusz Jankowski; Maria Marlicz; Karolina Skonieczna-Zydecka; Patrycja Krynicka; Igor Loniewski; Jerzy Samochowiec; Grażyna Rydzewska; George Koulaouzidis (Gastroenterology Review)
Burnout is common among physicians; it severely alters their health and has a negative impact on functioning of healthcare systems. Hypertension, increased cortisol levels, maladaptive behaviors with negative social consequences, and suboptimal quality of care have been associated with healthcare providers’ burnout. As the number of patients with cancers, psychiatric and neurodegenerative disorders will rise, we need new solutions to maintain physicians’ health and, therefore, quality of care. Coping strategies before the COVID-19 pandemic seem ineffective in scaling all the deficits of the global healthcare systems. Examples of new initiatives include new collaborative projects, such as COH-FIT (The Collaborative Outcomes study on Health and Functioning during Infection Times – https://www.coh-fit.com), which aims to collect global data and understand the impact of the COVID-19 pandemic on physical and mental health in order to identify various coping strategies for patients and healthcare workers during infection times, or MEMO (Minimizing Error, Maximizing Outcome), funded by the Agency of Healthcare Research and Quality (AHRQ). Others: i) Rome Foundation GastroPsych undertake efforts dedicated to the science and practice of psychogastroenterology, a burgeoning field with roots in behavioral intervention, cognitive science and experimental psychology focused on fostering the professional growth and collaboration of those engaged in medical practices, or ii) World Gastroenterology Organisation (WGO), Train The Trainers (TTT) program including a new topic of the impact of burnout on career longevity in order to foster strategies for staying healthy and increasing career satisfaction. There is a need for continuous development of digital technologies (e.g. training simulators, telemedicine, robots and artificial intelligence). Their implementation into medical practice is inevitable. Now more than ever, there is a need for a new spirit in healthcare. Together with others in the field, we believe this article is a desperate call for maximizing the use of novel technologies supported by collaborative interactions among healthcare providers and medical professionals of diverse medical fields.